The Impact of Nursing Home Environmental Expectation Gaps on Residential Adaptation Among Older Adults: Evidence from Inclusive Nursing Homes in Changchun, China - Boyu Du; Hang Zhang; He Liu; Wanying Qin; Xiaolong Zhao; Jinghao Zhao (Buildings, 2026)
This study examined how environmental expectation gaps, defined as discrepancies between older adults’ expectations before admission and their actual experiences after admission, are associated with residential adaptation in nursing homes. Survey data from 613 residents of six public and private inclusive nursing homes in Changchun, China, were analyzed using structural equation modeling and bias-corrected bootstrapping. Expectation gaps in safety and mobility convenience, privacy and autonomy, environmental comfort, and spatial cognition and familiarity were significantly associated with emotional adaptation, with spatial cognition and familiarity showing the strongest relationship. Support for activities and social interaction was positively associated with relationship formation but negatively associated with communal-living adaptation. Residential adaptation followed a sequential process from emotional adaptation to relationship formation, acceptance of institutional living, and adaptation to communal living. Bootstrap analysis further showed that several environmental expectation gaps were indirectly associated with later adaptation outcomes through this sequential process, with some direct and indirect relationships operating in opposite directions. These findings demonstrate that environmental expectation gaps are associated with residential adaptation through differentiated and interconnected pathways, extending nursing home evaluation beyond facility conditions and satisfaction alone.